Levels of oregano (Origanum vulgare) in the diet and its influence on the productive performance of the broiler - Pujada Abad, Hilario (2019)
The aim of this study was to determine the optimum level of oregano (Origanun vulgare) in the diet on the productive performance of broilers. A total of 120 1-day-old male chickens from the Cobb-500 line were randomly distributed in four treatments: 0, 0.5, 1.0 and 1.5% of dried and ground oregano in the diets. The final bodyweight, feed consumption and feed conversion were determined. Data was analysed by an analysis of variance through a completely randomized design and the Tukey test for the comparison of means. The polynomial regression and the derivative of a quadratic function were used to find the optimum level of oregano in the variables. The levels of oregano influenced bodyweight, feed consumption and feed conversion (p<0.05), denoting a quadratic effect. On average, the optimum level of oregano in the diet was 0.71%.